Empirical study on student’s cheating behaviour in higher education institution system using fraud diamond theory - Mohd. Noor, Rohana; Mat Dangi, Mohamad Ridhuan (UiTM Pahang, 2014)
This study investigates the cases of cheating in coursework assessments and examinations in a selected Higher Education Institution (HEI) and how it can be mitigated to ensure good and positive behaviour, morale and ethics of the future leaders. There are many types of cheating in examinations, which include plagiarism, use of materials such as short notes, use of IT gadgets such as mobile phone, and communication with others in the examination hall. Even though students were informed about the awaited punishments if they were caught cheating in an examination, there were still cheating cases reported by examination invigilators. In this study, the types of cheating cases among students are ranked accordingly. This is an empirical study adopting the main concepts in Fraud Diamond Theory, as each concept is similar to the factors that contribute to cheating behaviour among students. This study also highlights students‟ rationalization for cheating in coursework assessments and examinations.